The effect of lasers in occlusion of dentinal tubules and reducing dentinal hypersensitivity, a scoping review - Behnaz Behniafar; Faranak Noori; Nasim Chiniforoush; Amir Raee (BMC, 2024)
Abstract Background Dentinal hypersensitivity (DH) is a painful condition that can affect a person's quality of life. Laser therapy is a valid treatment option for this problem, which leads to immediate and long-term pain relief. This study aims to comprehensively review the effects of different laser treatments on DH. Methods The search was performed in electronic databases, including PubMed, Web of Science, Embase, Google Scholar, and Scopus, published in English from January 2012 to October 2024. The following keywords were searched: Laser, Dentine hypersensitivity, Dental pain. Relevant laboratory and clinical studies were included. Results Based on the electronic search, 988 articles were identified. Based on the search strategy and removal of duplicate articles, 47 articles remained. Finally, with the addition of 7 supplementary articles from a manual search, 16 in-vitro and 38 clinical studies were included. Application of high power diode laser at 980 nm and 2 W and Er;Cr:YSGG at a power of 0.5 W in a single session has been found to be a practical therapeutic approach in alleviating DH. The utilization of Nd:YAG was found to be inferior in high-power settings. Conclusion Both high/medium and low power lasers have the ability to relieve DH when used with appropriate output settings. These treatments demonstrate an instant pain-relieving effect upon application and also provide long-lasting advantages. Additionally, the simultaneous use of surface desensitizers, such as Gluma and substances that contain potassium nitrate with lasers, can be a practical approach for treating DH, especially when utilizing a low-power laser.